2002
DOI: 10.1074/jbc.m205395200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Targeting of Macromolecular Polyanions by an HIV-Tat Derived Peptide

Abstract: New therapies based on gene transfer and protein delivery require a better understanding of the basic mechanisms of macromolecular membrane transport. We have studied cellular uptake of macromolecular polyanions, i.e. DNA and glycosaminoglycans, and a polybasic HIV-Tat derived peptide (GRKKRRQRRRPPQC) using fluorescence assisted cell sorting and confocal fluorescence microscopy. The transactivator of HIV transcription (Tat) peptide stimulated cellular uptake of both DNA and heparan sulfate in a time-, concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
111
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(119 citation statements)
references
References 48 publications
8
111
0
Order By: Relevance
“…4C, black bars) suggests a more general role of GRP75 in nonclassical endocytosis. The HIV-TAT-derived transduction peptide, Tat, is a wellknown cell-penetrating peptide (CPP) previously shown to mediate DNA uptake through HSPGs (19). Consistent with a more general role of the GRP75-dependent endocytic pathway in macromolecular delivery, GRP75 inhibition reduced cellular uptake of CPP-DNA complexes, and scFv-αHS M colocalized with CPP-DNA complexes in vesicles (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…4C, black bars) suggests a more general role of GRP75 in nonclassical endocytosis. The HIV-TAT-derived transduction peptide, Tat, is a wellknown cell-penetrating peptide (CPP) previously shown to mediate DNA uptake through HSPGs (19). Consistent with a more general role of the GRP75-dependent endocytic pathway in macromolecular delivery, GRP75 inhibition reduced cellular uptake of CPP-DNA complexes, and scFv-αHS M colocalized with CPP-DNA complexes in vesicles (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…These saccharides could then form electroneutral membrane-penetrating complexes with small polybasic compounds such as spermine. Other studies from this laboratory have shown that a polybasic human immunodeficiency virus Tat-derived peptide is taken up by cells as a peptide-HS complex, followed by transfer of HS to the nucleus (42). Cell-surface PG molecules play a pivotal role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include the TAT peptide from the HIV transactivator protein TAT, Penetratin, a 16 amino acid domain from the Antennapedia protein of Drosophila, a flock house virus (FHV) coat peptide (sequence [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], and oligoarginines [3,5]. In this review, we focus on TAT peptide, partly because it has attracted the most attention, but also because it is a prototypical example that has many of the essential characteristics of the arginine-rich cell-penetrating peptides.…”
Section: Introductionmentioning
confidence: 99%